(untitled) (Applied Biological Research, 2012)
Nursery and field experiments were carried out to assess the effectiveness of N2-fixing bacteria, phosphate solubilizing bacteria and arbuscular mycorrhizal (AM) fungi, alone or in combination, on the growth and biomass production of pomegranate (Punica granatum). The study revealed significant improvement in nursery seedlings growth by biofertilizers use. Combined treatment of Azotobacter chroococcum + Glomus mosseae proved most effective in enhancing the rhizosphere microbial activity and concentration of various metabolites and nutrients in pomegranate in nursery experiments as well as helped in better plant establishment under field conditions. A significant improvement in plant height and fruit yield was observed in pomegranate plants under field conditions. Biofertilizer application also improved plant nutrient uptake and rhizosphere microbial activities. Results indicate that biofertilizer technology may be adopted for the establishment and development of horticultural plant species in rainfed agro-ecosystem.